On the Functional Overlap between Complement and Anti-Microbial Peptides - Zimmer, Jana; Hobkirk, James; Mohamed, Fatima; Browning, Michael J.; Stover, Cordula M. (Frontiers in Immunology, 2015)
Intriguingly, activated complement and antimicrobial peptides share certain functionalities; lytic, phagocytic and chemo-attractant activities and each may, in addition, exert cell instructive roles. Each has been shown to have distinct LPS detoxifying activity and may play a role in the development of endotoxin tolerance. In search of the origin of complement, a functional homologue of complement C3 involved in opsonisation has been identified in horseshoe crabs. Horseshoe crabs possess antimicrobial peptides able to bind to acyl chains or phosphate groups/saccharides of endotoxin, LPS. Complement activity as a whole is detectable in marine invertebrates. These are also a source of antimicrobial peptides with potential pharmaceutical applicability. Investigating the locality for the production of complement pathway proteins and their role in modulating cellular immune responses are emerging fields. The significance of local synthesis of complement components is becoming clearer from in vivo studies of parenchymatous disease involving specifically generated, complement deficient mouse lines. Complement C3 is a central component of complement activation. Its provision by cells of the myeloid lineage varies. Their effector functions in turn are increased in the presence of antimicrobial peptides. This may point to a potentiating range of activities which should serve the maintenance of health but may also cause disease. Because of the therapeutic implications, this review will consider closely studies dealing with complement activation and antimicrobial peptide activity in acute inflammation (e.g. dialysis-related peritonitis, appendicitis, ischemia).